PARP1 might enhance the therapeutic effect of tetrahydroxystilbene glucoside in traumatic brain injury via inhibition of Ras/JNK signalling pathway - Cao, Yiqiang; Chen, Yu; Wang, Fei; Wang, Yonggang; Long, Jiang (Folia Neuropathologica, 2020)
Trauma is the main cause of death for people aged 1-45, and among them, traumatic brain injury (TBI) is the major condition, which causes over 50,000 deaths each year and costs over 80 billion per year. Tetrahydroxystilbene glucoside (TSG) is the active ingredient of polygonum multiflorum, a traditional Chinese herbal medicine, which presented multiple pharmacological effects, including antioxidative, anti-inflammatory, reducing blood fat and neuroprotection effects. However, the effect of TSG in promoting the recovery of the nerve system after TBI is not fully understood. PARP1 is a key enzyme in repair of the damage in DNA, which is activated by binding to DNA breaks, initiating both single-strand and double-strand DNA break repair. And we thought that overexpression of TSG might enhance the effect of TSG in TBI treatment. In this study, we firstly detected the oxidative stress response related molecules in serum samples of TBI patients and a TBI mice model, and found that oxidative stress response was activated after TBI, and TSG would reduce this effect. We further noticed that inflammation related molecules presented a similar trend with oxidative stress response related molecules. These results indicated that inflammatory response and oxidative stress processes were both activated after TBI, and reduced after TSG treatment. We further detected that the apoptosis related proteins and anti-oxidative proteins were increased after TSG treatment, and these effects were enlarged after overexpression of PARP1. We further noticed that these effects might be mediated by inhibition of the Ras/JNK signalling pathway. Thus, we thought overexpression of PARP1 might enhance the therapeutic effect of TSG in TBI treatment.